Conversational Language Patterns Among Students at Darul Falah 3 Islamic Boarding School in Jombang: A Sociolinguistic Study - Asya Lyra Chaza Fatka; Udjang Pairin (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe the pattern of language variation in the speech acts of students at the Darul Falah 3 Islamic Boarding School in Jombang using a qualitative approach through the method of communication ethnography. The research data consists of students' speech obtained through the technique of free listening and conversation (SBLC) and documentation in various communication situations in the Islamic boarding school environment. The results of the study indicate that students' communication is characterized by the use of diverse language variations, including Indonesian-Arabic, ngoko-krama, Javanese-English, Javanese-Indonesian, and kromo-ngoko. These variations emerge as a form of adaptation to the students' diverse linguistic backgrounds, communication situations, and social relationships between speakers. The use of Arabic serves as a marker of religious identity, the transition between ngoko and krama reflects an awareness of norms of politeness and social hierarchy, while code-mixing with English shows the influence of modernity and is used to create familiarity in casual interactions. Overall, the language variations in students' communication not only function as a means of conveying information, but also as a means of expressing identity, maintaining social relationships, and adapting to the norms prevailing in the Islamic boarding school environment, thus showing that students' linguistic practices are dynamic and contextual.